Chains Chains Chains : 25 Necklaces, Bracelets and Earrings - Gollberg, Joanna and Mornu, Nathalie (New York Lark Crafts, 2011)
While metal chains can be stunningly simple, they offer endless design options with tremendous variations in styles and forms. This book celebrates the chain as an eye-catching piece of jewelry in and of itself that takes the spotlight without any pendants, bangles, or charms
Include Illustration
Keywords: Metal-work -- Jewelry making